Utilization of Spent FCC Catalyst as Fine Aggregate in Non-sintered Brick: Alkali Activation and Environmental Risk Assessment - Zhang, Dandan; Fang, Shiping; Zhang, Hongzhe; Liu, Zhengwei; Zhang, Zhiyuan; Zhang, Shucai (Frontiers in Chemistry, 2021)
The study focuses on recycling spent fluid catalytic cracking (FCC) catalyst to produce catalyst-based non-sintered bricks (CN-brick) for recovery of its aluminosilicate components and solidification of heavy metals. The effects of Cement content (10-20%), FCC proportion (10-40%) and Activator type (NaOH/Na2SiO3/Na2SO4) on the performance of CN-brick were investigated in terms of mechanical strength and leaching behavior. The results show that the optimal binder system 20% Cement +Na2SO4 could promote the compressive strength up to 42.3 MPa; the optimal FCC catalyst proportion 20% could achieve the lowest porosity and water absorption. The microscopic mechanism of cementitious process was analyzed by XRD, FTIR and SEM, proving that C-S-H and Ettringite (AFt) are the two main hydration products of CN-brick. Na2SO4 is superior than NaOH or Na2SiO3 as an activator since Na2SO4 takes advantage of the aluminum-rich property of FCC catalyst and specifically promote the formation of needle-like AFt. Quantitative environmental risk assessment was carried out for CN-brick based on TCLP leaching test, NEN 7371 maximum availability test and Hazard Index (HI) identification, a final HI 0.0045 (<1.0) indicates an acceptable risk for environment and nearby residents as CN-bricks being utilized on roads for 30 years.